The sufficient prevention level in the model of epidemic - Tiešis , Vytautas (Lietuvos matematikos rinkinys, 1997)
The aim of the research was to determine the level of prevention necessary to stabilise the epidemic of diseases transmitted by close contact (e.g. sexually or by blood). A model of an infection spread was biult. A11 active individuals were divided into approximately homogeneous groups according to their activity, character of contacts, susceptibility and other parameters. In the model the system of differential equations describes transition among the groups depending on infection, prevention of natural demographic causes. The rate of testing on infection, the rate of disclosing of infected partners, the percentage of safe behaviour after disclosing as well as the percentage of protected casual contacts significantly influences on infection spread. Those parameters may be controlled or influenced by prevention means. The set of values of parameters necessary to stabilise the epidemic was determined. The model was applied for Lithuanian data of HIV/AIDS epidemic.